Croceicoccus bisphenolivorans sp. nov., a bisphenol A-degrading bacterium isolated from seawater. Issue 2 (25th February 2021) - Li, Jiangwei; Hu, Anyi; Lv, Min; Yu, Chang-Ping
Abstract : A bisphenol A-degrading bacterium, designated as strain H4 T, was isolated from surface seawater, which was sampled from the Jiulong River estuary in southeast PR China. Strain H4 T is Gram-stain-negative, aerobic, short rod-shaped, lacking bacteriochlorophyll a, motile with multifibrillar stalklike fascicle structures and capable of degrading bisphenol A. Growth of strain H4 T was observed at 24–45 °C (optimum, 32 °C), at pH 5.5–9 (optimum, pH 7.0) and in 0–7 % NaCl (optimum, 2 %; w/v) . The 16S rRNA gene sequence of strain H4 T showed highest similarity to Croceicoccus pelagius Ery9 T (98.7 %), Croceicoccus sediminis (98.3 %), Croceicoccus naphthovorans PQ-2 T (98.1 %) and Croceicoccus ponticola GM-16 T (97.6 %), followed by Croceicoccus marinus E4A9 T (96.7 %) and Croceicoccus mobilis Ery22 T (96.0 %). Phylogenetic analysis revealed that strain H4 T fell within a clade comprising the type strains of Croceicoccus species and formed a phyletic line with them that was distinct from other members of the family Erythrobacteraceae . The sole respiratory quinone was quinone 10 (Q-10). The predominant fatty acids (>5 % of the total fatty acids) of strain H4 T were summed feature 8 (C18 : 1  ω 6 c and/or C18 : 1  ω 7 c ), summed feature 3 (C16 : 1  ω 6 c and/or C16 : 1  ω 7 c ), C17 : 1  ω 6 c and C14 : 0 2-OH. The genomic DNA G+C content was 62.8 mol%. In the polar lipid profile, phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, two unidentified phospholipids, two sphingoglycolipids and three unknown lipids were the major compounds. Based on the genotypic and phenotypic data, strain H4 T represents a novel species of the genus Croceicoccus, for which the name Croceicoccus bisphenolivorans sp. nov. is proposed. The type strain is H4 T (=DSM 102182 T =MCCC1 K02301 T ).